The determinants and market reaction to Open Briefings: an investor relations option and evidence on the effectiveness of disclosure. (23rd September 2014) - Ferguson, Andrew; Scott, Tom
Abstract: Open Briefings are market announcements styled as question and answer transcripts from a mock analyst interview and run by Orient Capital, an investor relations consultant. We found that Open Briefings are used by both growth and mature firms, and that Open Briefings are significant market events at both the daily and intraday level. In addition, the positive abnormal return does not soon reverse, suggesting Open Briefings are used by investors. We contribute to the existing literature by finding a stronger market reaction for firms with greater incentives to increase market awareness.